Elucidation of critical period of crop weed competition in groundnut (Arachis hypogaea) under mid-hills of Meghalaya - Santosh Korav; Vishram Ram; Sujatha H. T.; Venkatesh Paramesh; Shankarappa Sridhara; Hosam O. Elansary; Ihab Mohamed Moussa (Cogent Food & Agriculture)
The experiment consisted of 12 treatments (weed interference until 15, 30, 45, 60, and 75 days after emergence (DAE), weedy until crop maturity, and weed-free until 15, 30, 45, 60, 75, and a weed-free until crop maturity) and the treatments were arranged in a randomized complete block design (RCBD) with three replications. This study indicated increased weed interference period reduced the pod yield by 6.5–36 and 0.7–32%, and haulm yield by 6.4 – 34 and 6.5 – 34% during rainy and winter season respectively. Further, reduction in total biomass production by crop due to weed interference declined the total nutrient uptake by crop, i.e. nitrogen by 7.8–52.1 and 9.6–54.5%, phosphorus by 4.8–45.4 and 6–47.5%, potassium by 6.9–43.7 and 6.3–44.4%, sulphur by 18.4–53.3 and 18.8–53.9%, during rainy and winter season respectively. However, weed-free until crop harvest increased RUE by 293% and 314%, chlorophyll content by 8.7 and 10.7%, respectively, during rainy and winter seasons. This study indicated critical duration for crop-weed interference under 5% relative yield loss (RYL) was 16 to 66 DAE in rainy and 15 to 63 DAE in winter. Similarly, at 10%, RYL were 23 to 62 and 21 to 61 DAE, respectively, during the rainy and winter seasons. As a result, farmers should keep their groundnut crop weed-free between 15 and 66 DAE during the rainy and winter seasons.